2008
DOI: 10.1021/es702231g
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Natural Organic Matter on the Physicochemical Properties of Aqueous C60 Nanoparticles

Abstract: Existing toxicity data indicate that industrial-scale production of C60 fullerene poses a potential threat to the environment. Evaluating the environmental impact of C60 requires careful characterization of its physicochemical properties in the natural aqueous environment. Our study aims to determine the effects of aquatic natural organic matter (NOM) on the physicochemical properties of aqueous C60 nanoparticles, nC60. Stable nC60 suspensions were formed using three different solvent exchange protocols. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
152
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 39 publications
13
152
1
2
Order By: Relevance
“…2). It was not possible to determine in this study if aqueous nanoparticles were in dynamic equilibrium with the other phases or if they represented a static, solubilized reservoir of suspended particles 4,5 . Nanoparticles partitioned slowly into the sediments and were essentially equilibrated at the end of 12 days (Fig.…”
Section: Nmmentioning
confidence: 98%
See 1 more Smart Citation
“…2). It was not possible to determine in this study if aqueous nanoparticles were in dynamic equilibrium with the other phases or if they represented a static, solubilized reservoir of suspended particles 4,5 . Nanoparticles partitioned slowly into the sediments and were essentially equilibrated at the end of 12 days (Fig.…”
Section: Nmmentioning
confidence: 98%
“…As this region is also the habitat for many commercially and ecologically important shellfish and finfish, it could also be a critical point of nanomaterial contaminant entry into the marine food web. For example, salinity gradients, such as those found in tidal mixing zones, typically promote the flocculation and precipitation of organic matter and naturally occurring particulates 4,5 . Organic matter and particulates can be consumed by detritivores or shellfish, and they can also be a sink for anthropogenic material through burial in sediments 6 .…”
mentioning
confidence: 99%
“…NOM is mainly the residual from plants and animals materials, as well as some of the biocolloids mentioned before [15,22,58]. NOM has been shown to interact strongly with ENMs [59], modifying their surfaces and in general making them more bioavailable [60,61]. Therefore, it is important to understand the nature of NOM.…”
Section: Biocolloid Geocolloid and Natural Organic Mattermentioning
confidence: 99%
“…Hyung et al [24][25][26] investigated the effect of NOM on the aggregation of nanotubes and C 60 nanoparticles. Hoon et al reported that the stability of MWNTs in the aqueous was strongly dependent on the presence of natural organic matter (NOM).…”
Section: Characterization Of Nanoparticles and Their Complexesmentioning
confidence: 99%
“…The enhanced stabilities might be attributed to the aromatic fractions of NOM. Through thoroughly characterizing for particle size, morphology and electrophoretic mobility, Xie et al [25] found that NOM (Suwannee River humic acid and fulvic acid in paper) caused disaggregation of nC 60 crystal. So the sorption of HA may enhance the stabilities of SiO 2 and kaolinite in the aqueous system, thus cut down the size of nanoparticle aggregates to a certain extent.…”
Section: Characterization Of Nanoparticles and Their Complexesmentioning
confidence: 99%